Exploring Spatial Boundaries and Power Relations in John Boyne’s The Boy in the Striped Pyjamas - Titin Maharani; Imas Istiani (Anaphora : Journal of Language, Literary, and Cultural Studies, 2026)
This study examines how spatial organization and physical boundaries function as instruments of dehumanization in John Boyne’s The Boy in the Striped Pyjamas. Although spatiality has received increasing attention in literary studies, the relationship between the production of space and power in Holocaust narratives remains underexplored, particularly through the combined application of Henri Lefebvre’s and Michel Foucault’s theories. This study aims to analyze how spatial boundaries are represented in the novel and how spatial division operates as a mechanism of power, surveillance, and control over oppressed individuals. Using a qualitative descriptive-analytical approach, this research integrates Lefebvre’s theory of the Production of Space and Foucault’s concept of disciplinary power. Lefebvre’s framework explains how space is socially produced and ideologically shaped by dominant authorities, while Foucault’s perspective examines how spatial arrangements function as technologies of surveillance, discipline, and control. The findings reveal that walls, barbed-wire fences, bedroom windows, trains, and the airtight room symbolize the Nazi regime’s systematic dehumanization. From Lefebvre’s perspective, these spaces represent conceived space, where ideological planning and institutional authority sustain domination and social exclusion. From Foucault’s perspective, spatial division functions as a disciplinary mechanism through identity standardization, characterized by striped pyjamas, hierarchical surveillance, and biopower. This study contributes to literary studies by demonstrating that integrating Lefebvre’s spatial theory and Foucault’s disciplinary power provides a comprehensive framework for interpreting dehumanization in Holocaust fiction while expanding the application of spatial-power theory to the analysis of institutional control, spatial violence, and systematic oppression.